Expression, purification, immunogenicity, and protective efficacy of a recombinant Tc24 antigen as a vaccine against Trypanosoma cruzi infection in mice. Issue 36 (26th August 2015) - Martinez-Campos, Viridiana; Martinez-Vega, Pedro; Ramirez-Sierra, Maria Jesus; Rosado-Vallado, Miguel; Seid, Christopher A.; Hudspeth, Elissa M.; Wei, Junfei; Liu, Zhuyun; Kwityn, Cliff; Hammond, Molly; Ortega-López, Jaime; Zhan, Bin; et al.
Highlights: The Tc24 antigen from Trypanosoma cruzi is under evaluation as a vaccine candidate against Chagas disease. We developed a suitable platform for the large scale production of recombinant Tc24. Immunization of mice with rTc24 with a monophosphoryl-lipid A induces a Th1-biased immune response. Immunized mice were partially protected against an experimental infection. Abstract: The Tc24 calcium binding protein from the flagellar pocket of Trypanosoma cruzi is under evaluation as a candidate vaccine antigen against Chagas disease. Previously, a DNA vaccine encoding Tc24 was shown to be an effective vaccine (both as a preventive and therapeutic intervention) in mice and dogs, as evidenced by reductions in T. cruzi parasitemia and cardiac amastigotes, as well as reduced cardiac inflammation and increased host survival. Here we developed a suitable platform for the large scale production of recombinant Tc24 (rTc24) and show that when rTc24 is combined with a monophosphoryl-lipid A (MPLA) adjuvant, the formulated vaccine induces a Th1-biased immune response in mice, comprised of elevated IgG2a antibody levels and interferon-gamma levels from splenocytes, compared to controls. These immune responses also resulted in statistically significant decreased T. cruzi parasitemia and cardiac amastigotes, as well as increased survival following T. cruzi challenge infections, compared to controls. Partial protective efficacy was shown regardless of whether the antigen was expressed in Escherichia coli or in yeast ( Pichia pastoris ). While mouse vaccinations will require further modifications in order to optimize protective efficacy, such studies provide a basis for further evaluations of vaccines comprised of rTc24, together with alternative adjuvants and additional recombinant antigens.